Nanobiotechnology for green environment - Kumar, Amit (Assistant professor in biotechnology); Ram, Chhotu (Boca Raton : CRC Press, 2021)
The book examines environmental issues and their solutions with advancements in biotechnology and nanotechnology. This book will focus on environmental friendly waste management, wastewater treatment, and utilization of wastes for energy. As humanity is struggling for clean air, water and even contaminant free food, our society must ponder the condition of environment. This book covers a variety of environmental issues and how they could be solved through innovations in science, engineering and technology. The authors examine the use of biotechnological methods to remediate wastewater, toxic organic compounds and sludge management problems. The topics include different research disciplines such as water and wastewater treatment, solid waste management and utilization of wastes for energy. This book will be useful for researchers, students, scientists and academicians who are working in multidisciplinary areas like microbiology, biotechnology, nanotechnology to address environmental issues such as water and wastewater treatment, solid waste management and energy resources. Nanobiotechnology for Green Environment covers a variety of environmental issues and how they could be solved through innovations in science, engineering and technology.
OCLC-licensed vendor bibliographic record.
Keywords: Refuse and refuse disposal; Sewage sludge; Sewage; Nanobiotechnology; SCIENCE / Biotechnology